A case of adrenomyeloneuropathy caused by a novel point mutation in the ABCD1 gene and functional verification - Shi, Xiaoxue; Qi, Xuelin; Zheng, Jinhua; Ma, Jianjun; Li, Dongsheng (Frontiers in Genetics, 2024)
Adrenoleukodystrophy is a rare neurogenetic disease, and adrenomyeloneuropathy is the most common phenotype in adults. The clinical data of a patient with adrenoleukodystrophy and spinal-peripheral neuropathy caused by a novel point mutation in exon 4 of the ABCD1 gene (c.1256T>G (p.Val419Gly)) were retrospectively analyzed. Furthermore, we constructed wild-type and mutant vectors of the ABCD1 (NM0000334) gene to validate the effect of this mutation on the expression of the ABCD1 gene and protein and to explore the mechanism of X-linked adrenoleukodystrophy occurrence and development to identify therapeutic targets for clinical treatment.